Pengaruh Fee Audit, Audit Tenure, dan Rotasi Audit Terhadap Kualitas Audit - Fransiska Ede; Maulana Malik Muhammad (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study was conducted to examine the effect of Audit Fee, Audit Tenure and Audit Rotation on Audit Quality. The sampling in this study of 26 financial companies listed in Indonesia Stock Exchange period 2017-2019 with purposive sampling method. Data obtained from the company’s financial statements that have been publication. The number of samples was obtained from 26 companies with total 78 sample.Quality audits in this study using a proxy public accounting firm size.The analysis technique that used in this study is logistic regression with a significance level of 5%. The results in this study indicates that (1) Audit Fee has significant positive effect on Audit Quality (2) Audit Tenure does not affect the Qualit of the audit, and (3) Audit Rotation does not affect the Quality of the Audit